Reclaiming the Past: Restoration of Personal and Communal History in Petals of Blood - Klimková Simona (Prague Journal of English Studies, 2018)
The implications of the colonialist discourse, which suggested that the colonized is a person “whose historical, physical, and metaphysical geography begins with European memory” (Thiong’o, 2009), urged postcolonial writers to correct these views by addressing the issues from their own perspectives. The themes of history and communal/national past thus play a prominent role in postcolonial literature as they are inevitably interwoven with the concept of communal identity. In Petals of Blood (1977), the Kenyan writer Ngũgĩ wa Thiong’o explores the implications of social change as brought about by the political and economic development during the post-independence period. This paper seeks to examine the crucial relation between personal and communal/national history and relate it to the writer’s views of principal legacies of colonialism. As Thiong’o states: “My interest in the past is because of the present and there is no way to discuss the future or present separate from the past” (Thiong’o, 1975). Clearly, the grasping of the past and one’s identification with it seems fundamental in discussing national development. As Ngũgĩ wa Thiong’o’s narratives are always situated in the realm of political and historical context, blending fiction with fact, this paper also aims to elaborate on the implications of his vision.